2021
DOI: 10.1021/acs.est.0c08127
|View full text |Cite
|
Sign up to set email alerts
|

Health and Economic Consequences of Lead Exposure Associated with Products and Services Provided by the Informal Economy

Abstract: In low- and middle-income countries (LMICs), the presence of an informal economy can lead to human exposure to toxic metals such as lead (Pb). This paper demonstrates the local health and economic benefits of modifying practices within the informal economic sector in Madagascar. Specifically, leaded components in 504 locally manufactured household water pumps were replaced with unleaded components. Prior to the intervention, 32% of the household systems exhibited lead concentrations above the World Health Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…35 On a local level, the health and economic consequences can run into the millions of dollars; however, targeted remediations to reduce exposure can have returns on investment of greater than 1000:1. 20 The need for sound management of chemicals and/or toxins, throughout their entire life cycle, 36 has been highlighted as "fundamental" to the advancement of all 17 Sustainable Development Goals (SDGs). 4,37 Achieving the SDGs will in large part help to reduce future lead exposures, though the projected growth of "green" technologies (e.g., electric vehicles and e-bikes) 38 provides an enduring source of complex mixtures of toxic metals 39 that often find their fate in LMICs.…”
Section: ■ Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…35 On a local level, the health and economic consequences can run into the millions of dollars; however, targeted remediations to reduce exposure can have returns on investment of greater than 1000:1. 20 The need for sound management of chemicals and/or toxins, throughout their entire life cycle, 36 has been highlighted as "fundamental" to the advancement of all 17 Sustainable Development Goals (SDGs). 4,37 Achieving the SDGs will in large part help to reduce future lead exposures, though the projected growth of "green" technologies (e.g., electric vehicles and e-bikes) 38 provides an enduring source of complex mixtures of toxic metals 39 that often find their fate in LMICs.…”
Section: ■ Backgroundmentioning
confidence: 99%
“…Lead exposures in high-income countries have historically occurred through the use of leaded gasoline, lead-based paint, and contaminated drinking water, with indoor dust (from lead paint) a persistent “reservoir” for lead exposure. , With regulatory and educational efforts driving reductions in many of these sources in higher-income countries, exposure via drinking water has taken on greater importance. LMICs have similar routes of exposure; however, reducing lead exposures in these locations is a unique problem for multiple reasons, including the typically unregulated, informal economies (that may employ child labor) driving everyday lead emissions/exposures, more recent phase-out of leaded gasoline resulting in higher levels of lead in soil and dust, , cultural and behavioral differences resulting in increased ingestion, , impacts of malnutrition on lead poisoning, a lack of access to healthcare, limited autonomy in health care decision making, and a lack of health promotion and disease prevention activities . Informal and rural water systems in LMICs have been identified as important sources, aligning with issues of drinking water contamination in higher-income countries .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aligns with the definition given by the United States National Institute of Environmental Health Services . Some notable areas of global environmental health are inadequate water, sanitation, and hygiene (WASH) services and practices, household air pollution due to the burning of solid fuels, and chemical pollution resulting from industrial malpractice (often in the informal sector , ). These issues are relevant in development, humanitarian response, and environmental justice settings and across multiple scales, from individual behaviors to trans-national policies.…”
Section: Introductionmentioning
confidence: 99%
“…A study observed that 51% of field measurements of Pb concentrations in this community were above the World Health Organization (WHO) provisional guideline of 10 µg/L in drinking water [ 5 , 8 ]. A recent study modeling the BLLs of children in Toamasina estimates that approximately 34% of Malagasy children in Toamasina may be at risk for elevated BLLs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%